1995
DOI: 10.1074/jbc.270.5.2403
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Chicken GPAT/AIRC Bidirectional Promoter for de Novo Purine Nucleotide Synthesis

Abstract: GPAT and AIRC encode two enzymes that catalyze steps 1 and 6 plus 7, respectively, of the de novo purine biosynthetic pathway. The chicken genes are closely linked and divergently transcribed from an approximately 230-base pair intergenic region. The promoter was scanned by deletion mutagenesis in a bireporter vector that allowed assay of transcriptional activity in both directions in transfected HepG2 and chicken LMH cells. Three classes of deletions were obtained: those affecting bidirectional transcription,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Gavalas and Zalkin (1995) reported that GPAT and ARIC genes, which catalyse the first and sixth steps in de novo purine synthesis were closely linked and divergently transcribed from intergenic regions of approximately 230 bp in chickens. Chen (2004), Chai et al (2005) chose AMPD1 gene as candidate gene and analysed a 500-bp fragment of this gene using PCR-SSCP method in different chicken breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Gavalas and Zalkin (1995) reported that GPAT and ARIC genes, which catalyse the first and sixth steps in de novo purine synthesis were closely linked and divergently transcribed from intergenic regions of approximately 230 bp in chickens. Chen (2004), Chai et al (2005) chose AMPD1 gene as candidate gene and analysed a 500-bp fragment of this gene using PCR-SSCP method in different chicken breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these combined results strengthen the idea that the basis of the differential regulation of these genes during latency may lie within the sequence of the regulatory element itself. fungi, and viruses, and a recent report indicates that more than 10% of the genes in the human genome may be divergently transcribed from such promoters (9,17,19,27,36,42,51,(53)(54)(55)(56)(61)(62)(63). These regulatory sequences fall into two general categories.…”
Section: Vol 78 2004mentioning
confidence: 99%
“…Some head-to-head genes are positively correlated and function in the same pathway, such as human collagen genes COL4A1/COL4A2 [1,13] and chicken genes GPAT/AIRC involved in de novo purine nucleotide synthesis [14]; some are coregulated in a common window of the cell cycle, such as murine genes RanBP1/Htf9-c [5,15]; some are coordinated to respond to induction signals, for example, human genes HSP60/HSP10 [16]. However, there are also some rare examples of negatively correlated head-to-head genes, such as mouse genes TK/KF [12].…”
Section: Introductionmentioning
confidence: 99%